AI-Driven Payment Personalization and Smart Payment Assistants: Reshaping the Digital Payment Landscape - Priya Das, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-driven payment personalization and smart payment assistants represent a transformative advancement in financial technology, merging sophisticated machine learning models with traditional banking infrastructure. These intelligent systems optimize transaction processing through contextual awareness, adapting to individual user behaviors while maintaining robust security protocols. From hyper-personalized recommendation engines to conversational interfaces, these technologies create seamless payment experiences by predicting user needs, preventing fraud, and suggesting optimal payment methods. The architecture combines transactional, behavioral, contextual, and financial profile data through multi-layered processing pipelines, while privacy-preserving techniques like federated learning and differential privacy protect sensitive information. Integration with legacy payment infrastructure poses challenges due to architectural mismatches, yet adapter layers successfully bridge technological generations. The future points toward cross-modal intelligence incorporating visual, voice, biometric, and IoT data, potentially eliminating explicit checkout processes in favor of ambient commerce experiences.
Keywords: Authentication; Encryption; Microservices; Personalization; Transaction